Paired Electrocatalytic Oxygenation and Hydrogenation of Organic Substrates with Water as the Oxygen and Hydrogen Source. (22nd May 2019) - Zhang, Peili; Sheng, Xia; Chen, Xiaoyu; Fang, Zhiyong; Jiang, Jian; Wang, Mei; Li, Fusheng; Fan, Lizhou; Ren, Yansong; Zhang, Biaobiao; Timmer, Brian J. J.; Ahlquist, Mårten S. G.; et al.
Abstract: The use of water as an oxygen and hydrogen source for the paired oxygenation and hydrogenation of organic substrates to produce valuable chemicals is of utmost importance as a means of establishing green chemical syntheses. Inspired by the active Ni 3+ intermediates involved in electrocatalytic water oxidation by nickel‐based materials, we prepared NiB x as a catalyst and used water as the oxygen source for the oxygenation of various organic compounds. NiB x was further employed as both an anode and a cathode in a paired electrosynthesis cell for the respective oxygenation and hydrogenation of organic compounds, with water as both the oxygen and hydrogen source. Conversion efficiency and selectivity of ≥99 % were observed during the oxygenation of 5‐hydroxymethylfurfural to 2, 5‐furandicarboxylic acid and the simultaneous hydrogenation of p ‐nitrophenol to p ‐aminophenol. This paired electrosynthesis cell has also been coupled to a solar cell as a stand‐alone reactor in response to sunlight. Abstract : Dynamisches Duo : NiBx @NF wurde sowohl als Anode als auch als Kathode in einer gekoppelten Elektrosynthesezelle zur Oxygenierung bzw. Hydrierung von organischen Verbindungen mit Wasser als Sauerstoff‐ und Wasserstoffquelle eingesetzt. In der Oxygenierung von 5‐Hydroxymethylfurfural und der gleichzeitigen Hydrierung von p ‐Nitrophenol (siehe Bild) wurden eine ausgezeichnete Umwandlungseffizienz und Selektivität beobachtet.